Researches on mobile IP position management based on multicast network collaboration - XUE Jian-sheng1; WAN Lin-yi1; WANG Guang-xing2 (Tongxin xuebao)
A method of mobile IP position management which uses group managing function in multicast was proposed.Mobile agent（MA） was set in each autonomous network to form a VPN that manage the position binding information of mobile nodes.By putting nodes together for communicating with mobile host to make a multicast tree,the position bind-ing information of mobile nodes was maintained through the collaborative work of each node in network.The storage structure of binding information table and the algorithm on how to manage mobile position binding information were de-signed.Simulation shown that the method proposed can make correspondent nodes understand mobile node’s care-of ad-dress（CoA） in real-time,decrease registration time and times,decrease transmission delay,for supporting real-time ser-vice wonderfully.At the same time,the loads of home agent and hosts are alleviated.The performance of mobile IP is op-timized.